Portuguese European Multidisciplinary Seafloor and Water Column Observatory Initiative - Carapuço, Mafalda Marques; Silveira, Tanya Mendes; Stroynowski, Zuzia; Miranda, Jorge Miguel (Frontiers in Marine Science, 2022)
The Atlantic dimension of Portugal, with c. 1 700 000 km2 maritime area, led to the prioritization of the European Multidisciplinary Seafloor and water column Observatory - Portugal (EMSO-PT) in the national scientific infrastructures’ roadmap. In this work we present the EMSO-PT initiative: a research consortium joining 15 research institutions, with the aim of implementing a network of multidisciplinary underwater observatories in the Atlantic, as well as laboratories and data processing support infrastructures. EMSO-PT´s priority is to generate continuous scientific data on marine environmental processes related to the interaction between the geosphere, biosphere, and hydrosphere, and to develop new sensors and platforms which will extend ocean monitoring in the near future. Monitoring variables will include biotic and abiotic variables of the ocean floor and water column, namely temperature, salinity, turbidity, acoustics, currents and dissolved oxygen. Data will be disseminated through EMSO-ERIC channels, allowing for the integration and open access of data acquired by all partners of EMSO-ERIC, and by the research community at large.